Cần ngay bây h ah .đề bài là tính gtri biểu thuc

Question

Cần ngay bây h ah .đề bài là tính gtri biểu thuc
can-ngay-bay-h-ah-de-bai-la-tinh-gtri-bieu-thuc

in progress 0
Euphemia 9 months 2020-10-31T04:10:00+00:00 1 Answers 61 views 0

Answers ( )

    0
    2020-10-31T04:11:19+00:00

    Đáp án:

    $\begin{array}{l}
    a)\sqrt {5 – 2\sqrt 6 }  + \sqrt {12}  + \dfrac{1}{2}\sqrt 8 \\
     = \sqrt {3 – 2\sqrt 3 .\sqrt 2  + 2}  + 2\sqrt 3  + \dfrac{1}{2}.2\sqrt 2 \\
     = \sqrt {{{\left( {\sqrt 3  – \sqrt 2 } \right)}^2}}  + 2\sqrt 3  + \sqrt 2 \\
     = \sqrt 3  – \sqrt 2  + 2\sqrt 3  + \sqrt 2 \\
     = 3\sqrt 3 \\
    b)\dfrac{{3\sqrt 2  – 6}}{{\sqrt 2  – 1}} + \dfrac{{6\sqrt 2  – 4}}{{\sqrt 2  – 3}}\\
     = \dfrac{{3\sqrt 2 \left( {1 – \sqrt 2 } \right)}}{{\sqrt 2  – 1}} + \dfrac{{2\sqrt 2 \left( {3 – \sqrt 2 } \right)}}{{\sqrt 2  – 3}}\\
     =  – 3\sqrt 2  – 2\sqrt 2 \\
     =  – 5\sqrt 5 \\
    c)\dfrac{{\sqrt 6  – \sqrt 8 }}{{\sqrt 3  – 2}} – \sqrt {3 – 2\sqrt 2 }  + \dfrac{1}{{1 + \sqrt 2 }}\\
     = \dfrac{{\sqrt 2 \left( {\sqrt 3  – 2} \right)}}{{\sqrt 3  – 2}} – \sqrt {{{\left( {\sqrt 2  – 1} \right)}^2}}  + \dfrac{{\sqrt 2  – 1}}{{2 – 1}}\\
     = \sqrt 2  – \left( {\sqrt 2  – 1} \right) + \sqrt 2  – 1\\
     = \sqrt 2 
    \end{array}$

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )